Polarographic Studies of Indium(III) and Thallium(I) Complexes with DL-?-Alanine+68 - SHARMA, VINITA; GUPTA, K.D. (Asian Journal of Chemistry, 2010)
The polarographic behaviour of indium(III) and thallium(I) with DL-α-alanine have been studied in aqueous as well as in 25 % ethanolwater (v/v) media using a dropping mercury electrode. Indium(III) reduces reversibly in aqueous media and quasi-reversibly in 25 % ethanol-water (v/v) media involving three electrons in all solutions, whereas Tl(I) reduces reversibly in both aqueous as well as in 25 % ethanol-water (v/v) media involving one electron transfer process. The reduction is found to be diffusion controlled in both cases. The E½r have been determined by Gellings method. DL-α-Alanine formed 1:1 and 1:2 metal:ligand complexes with In(III) at pH = 4-4.25 and with Tl(I) at pH = 6-6.5. The stability constants of In(III)- DL-α-alanine and Tl(I)-DL-α-alanine have been determined using Deford-Hume method at temperature 30 and 40 ºC. The values of ΔG, ΔH and ΔS at 30 ºC have also been reported.